Controversial Constitutive TSHR Activity: Patients, Physiology, and In Vitro Characterization - Huth, S.; Jaeschke, H.; Schaarschmidt, J.; Paschke, R. (Hormone and Metabolic Research, 2014)
G protein-coupled receptors constitute a large family of transmembrane receptors, which activate cellular responses by signal transmission and regulation of second messenger metabolism after ligand binding. For several of these receptors it is known that they also signal ligand-independently. The G protein-coupled thyroid stimulating hormone receptor (TSHR) is characterized by a high level of constitutive activity in the wild type state. However, little is known yet concerning the physiological relevance of the constitutive wild type TSHR activity. Certainly, knowledge of the physiological relevance of constitutive wild type receptor activity is necessary to better understand thyroid physiology and it is a prerequisite for the development of better therapies for nonautoimmune hyperthyroidism and thyroid cancer. Based on a literature search regarding all published TSHR mutations, this review covers several mutations which are clearly associated with a hyperthyroidism-phenotype, but interestingly show a lack of constitutive activity determined by in vitro characterization. Possible reasons for the observed discrepancies between clinical phenotypes and in vitro characterization results for constitutive TSHR activity are reviewed. All current in vitro characterization methods for constitutive TSHR mutations are “preliminary attempts” and may well be revised by more comprehensive and even better approaches. However, a standardized approach for the determination of constitutive activity can help to identify TSHR mutations for which the investigation of additional signaling mechanisms would be most interesting to find explanations for the current clinical phenotype/in vitro discrepancies and thereby also define suitable methods to explore the physiological relevance of constitutive wild type TSHR activity.
Keywords: TSHR; hyperthyroidism; constitutive activity; TSHR mutation